In Vitro Detection of Acaricidal Resistance Status of Rhipicephalus (Boophilus) microplus against Commercial Preparation of Deltamethrin, Flumethrin, and Fipronil from North Gujarat, India. (14th December 2015) - Shyma, K. P.; Gupta, Jay Prakash; Singh, Veer; Patel, K. K.
Abstract : Rhipicephalus (Boophilus) microplus is the most common tick species in India infesting cattle and buffaloes and causing significant economic losses to dairy and leather industries by adversely affecting the milk production and quality of hides. A study to evaluate the acaricide resistance status of Rhipicephalus (Boophilus) microplus to deltamethrin, flumethrin, and fipronil was conducted on the samples collected from organized and unorganized farms of North Gujarat state, where treatment failures were reported frequently. Adult Immersion Test (AIT) and Larval Packet Test (LPT) were conducted using field strain for determination of 50 and 95% lethal concentration of deltamethrin, flumethrin, and fipronil. Results obtained by the Adult Immersion Test showed low grade resistance (level I, RF > 5) has been developed against both deltamethrin and fipronil. However, deltamethrin by performing Larval Packet Test showed moderate grade resistance (level II, RF > 25). Larval packet performed by flumethrin also revealed low grade resistance, level I. The data on field status of acaricide resistance from the area with diversified animal genetic resources will be helpful to adopt suitable strategy to overcome the process of development of resistance in ticks.